Animal health beyond the single disease approach – A role for veterinary herd health management in low-income countries?. (May 2021) - Gertzell, Elin; Magnusson, Ulf; Ikwap, Kokas; Dione, Michel; Lindström, Lisa; Eliasson-Selling, Lena; Jacobson, Magdalena
Abstract: In order to identify and evaluate health related constraints faced by Ugandan pig farmers, a veterinary herd health management approach (VHHM) was applied in 20 randomly selected pig farms in the Lira district, Uganda. Regular herd visits were conducted between July 2018 and June 2019, using e.g. interviews, observations, clinical examinations and laboratory analyzes to gather qualitative and quantitative data on relevant aspects of the production. The pig farmers kept on average 18.6 pigs, including 2.6 sows/year. The production figures varied considerably but were generally poor. The sows produced 1.6 litters/year and 8.2 piglets born alive per litter, the average daily gain was 101 g/day, and the mortality in growers was 9.7%. Four major constraints were identified; poor nutrition, infectious diseases, inferior biosecurity, and poor reproductive management. The quantity and quality of feed was suboptimal. Endo- and ectoparasites were very common, causing diarrhea, bronchitis, pneumonia, skin lesions and pruritus. Post-weaning diarrhea associated with enterotoxigenic Escherichia coli was important in the two largest herds, and parvoviral antibodies were found in seven herds, two experiencing problems with mummified fetuses. Biosecurity practices were insufficient and inconsistent, with free-ranging pigs and the use of village boars being the major risks. Reproductive figures were affected by poor estrus detection and service management. Overall, farmers lacked important knowledge on good management practices. In conclusion, the VHHM identified several important constraints that should be addressed in order to increase the productivity of Ugandan pig herds. Highlights: The pig production in Uganda is hampered by health and productivity constraints. Veterinary herd health management may be used to assess these. Poor biosecurity and infectious diseases are common, e.g. endo- and ectoparasitosis. Poor nutrition and management are other important constraints.